2012
DOI: 10.1111/j.1536-7150.2012.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Corn and Mexican Agriculture: What Went Wrong?

Abstract: The debt crisis of the 1980s caused the development strategy pursued by the Mexican government to be subject to a radical adjustment process that triggered deep repercussions for the agricultural sector and its farmers, particularly in the corn sector. In combination with the aggressive agricultural policies sustained by the U.S. government, the new approach meant that Mexican agriculture operated within an economic environment characterized by significant asymmetries and distortions, some internal and some im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The main objectives of PROCAMPO were to improve domestic and international competitiveness in the private and social sector, improve the livelihood of rural families and modernize the marketing system by providing financial resources to stimulate the production of crops more profitable than maize (Pérez-Soto et al, 2016;Zarazúa-Escobar et al, 2011). In practice, the program gave financial support to farmers in proportion to the acreage of particular crops (Avalos and Graillet, 2013;Klepeis and Vance, 2003;Sweeney et al, 2013). PROCAMPO changed its name in 2014 to PROAGRO (SAGARPA 2016), but we only refer to PROCAMPO in this article.…”
Section: Policies Affecting Changementioning
confidence: 99%
See 1 more Smart Citation
“…The main objectives of PROCAMPO were to improve domestic and international competitiveness in the private and social sector, improve the livelihood of rural families and modernize the marketing system by providing financial resources to stimulate the production of crops more profitable than maize (Pérez-Soto et al, 2016;Zarazúa-Escobar et al, 2011). In practice, the program gave financial support to farmers in proportion to the acreage of particular crops (Avalos and Graillet, 2013;Klepeis and Vance, 2003;Sweeney et al, 2013). PROCAMPO changed its name in 2014 to PROAGRO (SAGARPA 2016), but we only refer to PROCAMPO in this article.…”
Section: Policies Affecting Changementioning
confidence: 99%
“…A shift to neoliberal directives in the 80s, culminating in the General Agreement on Tariffs and Trade (GATT) in 1986 and the North American Free Trade Agreement (NAFTA) in 1994, had several effects on poor rural areas (González and Alferes, 2010;Klepeis and Vance, 2003;Sweeney et al, 2013). The GATT and NAFTA impacted households directly or indirectly by triggering shifts in government support to farmers (Winters and Davis, 2009), facilitating the commercialization of land (Echanove Huacuja, 2016), reducing prices of agricultural product (Barnes, 2009;Nicita, 2004), increasing migration (Taylor et al, 1999), and leading farmers to diversify their income through off-farm activities (Avalos and Graillet, 2013;Patel and Henriques, 2003). Considering the diversity in agricultural systems and socio-ecological contexts in Mexico (Appendini et al, 2008;Speelman et al, 2014), it is safe to expect that a particular driver of change will not have the same impact on each household.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results showed that across the 30 years households continued to produce maize and crop diversity did not change markedly. Many households produced maize for self-consumption (Avalos and Graillet, 2013). In Brazil, a plan known as "Brasil sem miséria" (Brazil without extreme poverty) was implemented that focused on both improving food production for self-consumption and the socio-economic conditions of poor rural households.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the program gave financial support to farmers in proportion to the acreage of particular crops (Avalos and Graillet, 2013;Klepeis and Vance, 2003;Sweeney et al, 2013). PROCAMPO changed its name in 2014 to PROAGRO (SAGARPA, 2016), but we only refer to PROCAMPO in this article.…”
Section: Policies Affecting Changementioning
confidence: 99%
See 1 more Smart Citation